Association of XRCC2 rs2040639 with the survival of patients with oral squamous cell carcinoma undergoing concurrent chemoradiotherapy - Senghore, Thomas; Wang, Wen-Chang; Chien, Huei-Tzu; Chen, You-Xin; Young, Chi-Kuang; Huang, Shiang-Fu; Yeh, Chih-Ching (Gene, 2021)
•XRCC2 rs2040639 is associated with advanced oral squamous cell carcinoma survival.•The A-allele of XRCC2 rs2040639 exhibited a decreased risk for recurrence.•Carrying A-alleles of XRCC2 rs2040639 and PRKDC rs7003908 decreased recurrence risk. To investigate the association between the variants of DNA double-strand break repair genes and the clinical outcomes of patients with oral squamous cell carcinoma (OSCC) undergoing concurrent chemoradiotherapy. Five variants of DNA double-strand break repair genes in samples from 319 patients with OSCC were genotyped using the Sequenom iPLEX MassARRAY system. Kaplan–Meier curves and Cox proportional hazards analysis were used to identify the factors associated with patient survival. The XRCC2 rs2040639 (G3063A) polymorphism in the codominant model was associated with decreased recurrence risk (hazard ratio [HR] = 0.55, 95% confidence interval [CI] = 0.31–0.98; p = 0.042). A marginally significant interaction was observed between XRCC2 rs2040639 and PRKDC rs7003908 in patients carrying the AA and AA genotypes; these patients showed reduced recurrence risk (HR = 0.36, 95% CI = 0.17–0.79; p = 0.010). The A-allele of XRCC2 rs2040639 is a favorable prognostic factor for disease-free survival. Patients with these genotypes may benefit from concurrent chemoradiotherapy. Additional confirmation from studies with larger samples or other ethnic populations is warranted.